2019
DOI: 10.3390/su11061790
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Higher Education Levels on Total Factor Productivity Growth

Abstract: China is facing challenges to sustainable economic growth. Higher education of Chinese residents can affect total factor productivity (TFP) growth and hence has an influence on economic sustainability. However, currently, there is limited literature on the nexus between higher education and TFP in China. Therefore, this paper empirically analyzes the heterogeneous and spatial effect of higher education on the regional TFP growth using a dynamic spatial econometric model with provincial panel data from 2003 to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 31 publications
6
16
0
Order By: Relevance
“…This result provides evidence of the positive effect between the two. The result of the positive effect is in line with the theoretical expectation, which shows that positive lagged values are likely to produce positive effects on the current values, due to persistence effects (Liu and Bi 2019;Espoir and Ngepah, 2020).…”
Section: Results Of Static and Dynamic Panel Modelssupporting
confidence: 84%
See 1 more Smart Citation
“…This result provides evidence of the positive effect between the two. The result of the positive effect is in line with the theoretical expectation, which shows that positive lagged values are likely to produce positive effects on the current values, due to persistence effects (Liu and Bi 2019;Espoir and Ngepah, 2020).…”
Section: Results Of Static and Dynamic Panel Modelssupporting
confidence: 84%
“…However, a static panel model provides inaccurate results in the presence of dynamic and persistent effects of time-series. An inclusion in the model of one or two lags of the dependent variable allows accounting for the dynamism and persistence effects of time-series (Liu & Bi, 2019). Henceforth, we extended Eq.…”
Section: The Model 411 Model Without Spatial Considerationsmentioning
confidence: 99%
“…Furthermore, the first period lag of TFP has a positive and statistically significant effect on the current values of TFP. This positive effect is in line with the theoretical expectation which shows that positive lagged values are likely to produce positive effects on the current values of TFP, due to persistence effects (Liu and Bi 2019).…”
Section: Econometric Resultssupporting
confidence: 90%
“…When the spatial weighting matrix is defined to represent the spillover effects based on an economic distance approach, as in the case of this study, it can be found to be time-varying, and quite often endogenous, in spatial panel data models (Liu and Bi 2019). In most cases, the estimation process leads to estimation bias.…”
Section: Robustness Checkmentioning
confidence: 97%
“…Liu and Bi has researched the influence of production factors on higher education (Liu & Bi, 2019) and Crespo has examined the role of education with sustainable development (Bárbara et al, 2017).…”
Section: Science Education and Economic Growthmentioning
confidence: 99%